Regulatory and Structural limits to the Justiciability of Economic, Social and Cultural Rights or Good Living Rights in Ecuador - Escudero Soliz, Jhoel (2020)
This article conducts a study on the achievements perceived in the recognition of Economic, Social and Cultural Rights (ESCR) or good living rights and the limits that affect their exercise and justiciability. These problems are scarcity and pover-ty; the cost of ESCR; poor public policies effectiveness; the obstacles of a judicial system based on private property; and the noncompliance of rulings that recogni-ze these rights. To highlight difficulties of exercising these rights, three relevant ca-ses are analysed through a deductive methodology. The Constitutional Court of Ecuador, between 2008 and 2019, addressed these cases due to their seriousness. They reflect a correlation with structural inequality and show that the victims, al-beit  obtained  a  favourable  ruling,  they  were  not  able  to  fully  exercise  their  right  to housing, health, and social welfare, which are essential to accomplish a mini-mum degree of dignity or good living, as is stated by the Ecuadorian Constitution.